Neser and shuluk-chugaa: Variants of prosopoetic synthesis in Tatar and Tuvan literatures - Amineva, Venera R.; Mizhit, Lyudmila S. (The New Research of Tuva, 2023)
The authors specify the types of interaction between poetic and prose strategies for artistic thinking in Tatar and Tuvan literatures using the cases of neser by Shamil Anak (1928–2005) and Ramziia Gabdelkhakova (b. 1959) as well as shuluk-chugaa by Eduard Mizhit (b. 1961) and Alexander Darzhay (1944–2016). The article highlights parameters of the ethnic and cultural identity of the genres of neser and shuluk-chugaa. They are typologically close, but have different origins in Tatar and Tuvan literatures: in Tatar literature, the genre form of neser goes back to the medieval literatures of the East where rhythmic prose (saj') was widespread, and in the works of contemporary Tuvan writers, shuluk-chugaa appears as a result of the transgression of the genre, mainly typical of French literature.The research into the poetics and features of the functioning of neser and shuluk-chugaa in the Tatar and Tuvan literatures of the late 20th and early 21st centuries is based on the criteria established in literary studies for distinguishing poetry and prose as formal and substantive categories.It has been found out that both Tatar and Tuvan writers use similar techniques for poetization of prose texts. A distinctive feature of E. Mizhit’s prose miniatures and elegies-neser by Sh. Anak is the influence of poetic structures reflecting the characteristics of mythological thinking on the depicted world. Generalization of the emotional and psychological experience of lyrical subjects is carried out on the ways of symbolization of the subject matter. In neser by Sh. Anak and R. Gabdelkhakova, rhythm-forming function is performed by the method of paradigmatization of the text and the introduction of a network of equivalences into it. These equivalences are manifested both in terms of content and in terms of expression. Poems in prose by E. Mizhit are prosimetric works. Their integrity creates the complementarity of poetic and prosaic artistic worldviews. The expansion of the synthesizing possibilities of prose miniatures in Tuvan and Tatar literatures is demonstrated by the case of the works by A. Darzhay (in his writings, shuluk-chugaa functions as a capacious and flexible artistic form that incorporates elements of a parable) and R. Gabdelkhakova (in her prose, neser exists as a lyric and epic work where the leading role belongs to the lyrical trend).The conducted research makes it possible to clarify and deepen our understanding of genre processes in Tatar and Tuvan literatures as well as to characterize a kind of micromodel of the inter-literary process presented in its synchronic aspect.
Keywords: Tatar literature; Tuvan literature; genre; symbol; mythological semantics; rhythm; literary mode; extramodal form; extra-artistic element